COMPARISON OF AMBULATORY AND INPATIENT CLEFT LIP SURGERY FOR ADULTS - Sohail, Muhammad; Khan, Farid Ahmad; Mir, Zameer Abbas (Journal of Ayub Medical College Abbottabad, 2010)
Background: Ambulatory cleft lip repair after its acceptance in developed countries is also becoming popular in developing world. This study was performed to compares the outcomes of ambulatory cleft lip repair with the inpatient group for adult patients. Objectives were to compare outcome after ambulatory and inpatient cleft lip surgery for adults with respect to perioperative complications (Early: pain, oedema of upper lip, bleeding, nausea or vomiting, infection, dehiscence; Late: visible scar and white roll discrepancy), to compare the economic benefits, and evaluate patient satisfaction in terms of acceptance for ambulatory surgery. Methods: This comparative study is carried out in Plastic Surgery Department, King Edward Medical University, Mayo Hospital, Lahore. The study included 80 adult patients fulfilling inclusion criteria and were randomly divided into two groups, i.e., Ambulatory (Group-A, n=40) and Inpatient (Group-B, n=40). Those belonging to ambulatory group were worked up on OPD basis, advised to report on morning of surgery, operated under loco-regional anaesthesia and were discharged on same day. Patients of inpatient group were admitted two days before surgery, worked up in ward, operated under general anaesthesia and were discharged on 2nd day. Results: Ambulatory cleft lip surgery can be easily performed under loco-regional anaesthesia. Perioperative complications between these groups were comparable. Hospital stay was significantly reduced in ambulatory surgery. The patients felt more satisfied after ambulatory than inpatient surgery. Conclusion: Ambulatory cleft lip repair for adults is as safe as inpatient surgery. It is dependable option and can be successfully performed in our setup. It should be considered whenever possible due to cost effectiveness, reduction of waiting lists, earlier discharge and better utilisation of hospital resources. Keywords: Cleft lip, Ambulatory surgery, Inpatient surgery, local anaesthesia